SOCIAL WELL-BEING OF THE STAVROPOL INHABITANTS AS AN INDICATOR OF ADAPTATION TO MODERN CONDITIONS OF RUSSIA - Maria A. Nichegovskaya (Вестник Северо-Кавказского федерального университета)
In this article the most acute and complicated problems of the modern society in the socio-economic sphere are allocated, the causes of the adaptation process are disclosed.